Accessibility for disabled in Klang and KL transport terminal / Mashita Sham - Sham, Mashita (2014)
Accessibility to public buildings especially transport terminals is paramount in our daily lives, what more when dealing with external and internal environment. Realising that most public transportation terminal in Malaysia are having the scarcity in terms of the satisfaction of quality in their designs and facilities, serious is indeed in need to be dissected to find the best solution that offers the best of convenience to all users. The aim of this research is to determine the impact of current infrastructure design to the disabled specifically concerning the accessibility aspect in public transportation terminals. The objective of this study is to evaluate the interior and exterior infrastructure for the accessibilities of PWDs, focusing specifically on the two selected main public terminals in the Klang Valley namely the Klang Sentral and the KL Sentral. This study utilise quantitative method as it involves questionnaire surveys on public transport commuters for the disabled where the samples is taken from the two selected terminals. The data collected were analyzed using Statistical Package for Social Science (SPSS). On-site audit survey was also conducted by the researcher. The findings of this research indicated that different types of disability requires different infrastructure provisions for a good accessibility at public transportation terminals. This research significantly promotes and enhances on affable facilities and designs for the disabled which will consequently promote better atmosphere Conclusively, it is observed that most of the facilities were design without compliance with the Universal Design (UD) standard and Malaysian Standard (MS).